Pengaruh Aplikasi Sistem Informasi Akuntansi, E-commerce dan Digital Marketing terhadap Profitabilitas UMKM di Kota Bandar Lampung - Muhammad Abdillah; Pigo Nauli (AKUNTANSI 45, 2026)
The profitability of Micro, Small, and Medium-Sized Enterprises (MSMEs) in Bandar Lampung City is examined in connection to the usage of Accounting Information Systems (AIS), e-commerce, and digital marketing. Using primary data from questionnaires given to MSME owners and managers, a quantitative research approach is used. Structural Equation Modeling (SEM) with a Partial Least Squares (PLS) method is used to examine the data. The results show that MSME profitability is not greatly impacted by AIS implementation. This result suggests that AIS is currently mostly utilized for standard administrative and record-keeping duties, suggesting that it is not yet fully utilized as a strategic tool in practice. On the other hand, digital marketing and e-commerce both show a significant increase in profitability. Their capacity to increase market access and boost sales success is a clear indication of their impact. These findings demonstrate that technology by itself is not enough to enhance company success. The effectiveness with which digital tools are used in day-to-day company operations determines their advantages. Therefore, in order to guarantee that AIS and other digital technologies can be used more strategically to assist the financial performance of MSMEs, improving digital literacy and bolstering users' technical capabilities are essential tasks.